Sulphur and Phosphorus Interaction in Nutrition of Indian Mustard (Brassica juncea L.) under Cold Arid Conditions of Ladakh - Thakur, S K; Bhat, A K; Samanta, A (Annals of Arid Zone, 2016)
Short Communication